The long-term impact of effective teaching. Issue 2 (3rd April 2018) - Tymms, Peter; Merrell, Christine; Bailey, Katharine
ABSTRACT: This paper investigates the impact of effective schooling in the 1st year of elementary school on later academic outcomes and equal educational opportunity. A large longitudinal dataset from England was used to estimate the importance of the 1st year of elementary school for academic outcomes up to age 16. Multilevel models, controlling for baseline assessment, deprivation, sex, and ethnic status, showed that classes in the 1st year differed substantially in their progress but did not vary in their impact on equity. Those classes defined as effective and students from those classes were tracked on 3 further occasions up to the age of 16 and compared with others. Being in an effective class in the 1st year of school, when the children were aged 4 to 5 years, was significantly related to later attainment at age 16 (Effect Size = 0.2). However, it was unrelated to equity at age 16.